2016
DOI: 10.2224/sbp.2016.44.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Does Customer Value Creation Behavior Drive Customer Well-being?

Abstract: To address the potential ambivalent effects of customer value creation behavior (CVCB) in a service setting, we developed a theoretical model identifying separate psychological mechanisms that account for both positive and negative effects of CVCB on customer outcomes, such as customer value and customer well-being. Participants comprised 103 business customer–supplier dyads. The results show that CVCB enhanced customer outcomes through the intermediate mechanism of customer self-determination, but hindered c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 0 publications
1
27
1
Order By: Relevance
“…While prior research showed a positive direct relationship between customer participation and well-being for other service categories (e.g. Gong et al , 2016; Hsieh et al , 2018; Sweeney et al , 2015), the findings did not reveal the underlying mechanism and thus may not fully reflect the nature of mental stimulus processing services. In particular, mental stimulus processing involves intangible actions to customers' minds rather than their bodies or financial assets.…”
Section: Introductioncontrasting
confidence: 70%
See 3 more Smart Citations
“…While prior research showed a positive direct relationship between customer participation and well-being for other service categories (e.g. Gong et al , 2016; Hsieh et al , 2018; Sweeney et al , 2015), the findings did not reveal the underlying mechanism and thus may not fully reflect the nature of mental stimulus processing services. In particular, mental stimulus processing involves intangible actions to customers' minds rather than their bodies or financial assets.…”
Section: Introductioncontrasting
confidence: 70%
“…Anderson et al (2013) posited that life satisfaction, positive affect and the absence of negative affect are key aspects of hedonic well-being. In line with this view, prior empirical research has demonstrated the influence of services on financial well-being (Guo et al , 2013; Losada-Otalora et al , 2018; Mende and van Doorn, 2015), quality of life (Gong et al , 2016; Sweeney et al , 2015) and happiness (Hsieh et al , 2018). Financial well-being is related to the customers' economic self-sufficiency, quality of life is a cognitive judgment of the customer's life situation and happiness reflects the affective aspects of well-being.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The reason behind this is to create a motivation for consumers' need, loyalty and profitability. Gong et al (2016) show and confirmed that the consumer is indeed a value maker. Their study was based on the value itself, the wishes of the consumer and the quality of the relationship between consumer and supplier.…”
Section: Introductionmentioning
confidence: 53%